Positive Solutions for Higher Order Nonlocal Fractional Differential Equation with Integral Boundary Conditions. (1st October 2018) - Jiang, Jiqiang; Liu, Weiwei; Wang, Hongchuan
Abstract : In this paper, by using the spectral analysis of the relevant linear operator and Gelfand's formula, some properties of the first eigenvalue of a fractional differential equation were obtained; combining fixed point index theorem, sufficient conditions for the existence of positive solutions are established. An example is given to demonstrate the application of our main results.